2020
DOI: 10.33495/jacr_v8i6.20.154
|View full text |Cite
|
Sign up to set email alerts
|

Application of modern estrus detection protocols in small scale Hybrid Black pig production systems

Abstract: The aim of this study was to re-invent the readily available estrus detection methods in small scale with black colour pigs, capable to yield more accurate results. Data were collected from 32 Meishan X Large Black X Duroc Hybrid Black sows housed in groups. Weaned sows were observed for 11 days, and estrus was detected twice daily, comprising of live observations of mating behaviour, a boar test and a back pressure test. The findings revealed a strong inverse relationship (r = -0.885) between time spent on ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…As far as we have been able to find in the literature, this is the first work to study the circadian cycle of sows during the post-weaning period until service. So far, much emphasis has been placed on the use of skin, rectal or vaginal temperature to determine sow [ 7 , 10 ] or cow [ 14 , 22 ] oestrus or ovulation timing, but the circadian parameters of this period have not been described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we have been able to find in the literature, this is the first work to study the circadian cycle of sows during the post-weaning period until service. So far, much emphasis has been placed on the use of skin, rectal or vaginal temperature to determine sow [ 7 , 10 ] or cow [ 14 , 22 ] oestrus or ovulation timing, but the circadian parameters of this period have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Research in this field has mainly been conducted in humans, where the circadian temperature rhythm has been linked to metabolism [ 1 ], aging and physical activity [ 2 ], thermoregulatory capacity [ 3 ] or reproduction [ 4 , 5 ]. Another important point is the acquisition of temperatures, both core and skin, since the first approaches with classical thermometry (rectal or vaginal), have moved on to the use of non-contact elements such as infrared thermography [ 6 – 10 ], or the use of continuous recording devices such as Thermocron [ 11 ], bio-loggers [ 12 ] or encapsulated radiotransmitters [ 13 ] implanted subcutaneously, intraperitoneally or intravaginally [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different approach, considering the effect of ambient temperature, simultaneously observing the temperature change of vulva and other body parts (gluteal area, udder, and ear base), or the temperature difference change between these body parts and vulvar skin temperature. The results showed that changes in vulvar skin temperature were the most correlated with estrus and that the mean temperature of vulvar skin of gilts and multiparous sows increased at the onset of estrus and decreased before ovulation [3,[23][24][25] . Moreover, the validity of vulvar skin average temperature variation as a predictor of sow ovulation was evaluated by inseminating sows once when the vulvar skin temperature of diestrous sows was 20% increased [1] or below 35°C [26] , where the threshold of 35°C resulted from Luño et al [18] The results showed comparable reproductive performance with the multiple insemination strategy of the conventional back-pressure test.…”
Section: Introductionmentioning
confidence: 99%